PENGARUH PROGRAM EDUKASI TERINTEGRASI TERHADAP PERILAKU PASIEN PASCA STROKE YANG DIRAWAT DI RSUD LUBUK SIKAPING - isnadi agus (Universitas Fort De Kock, 2021)
Healthy living behavior in post-stroke patients is still relatively low so that the residual symptoms experienced by patients are quite varied. Integrated education is one of the efforts that can be given to improve patient's healthy behavior where education is provided by the collaboration of Caregiver Professionals (PPA) consisting of doctors, nurses, pharmacists and nutritionists so that patients can make the right decisions to optimize their health and improve patient safety, satisfaction patients and families. The purpose of this study was to see the effect of an integrated education program on the behavior of post-stroke patients. This type of research is a quantitative study with aresearch design Quasy Experimental Pre-Post Test One Group with a sample of 38 people. This research was conducted at Lubuk Sikaping Hospital. The data collection tool uses a questionnaire. Data analysis was carried out using thetest Wilcoxcon. The results of the study illustrate that there is a significant difference between the knowledge, attitudes and actions of post-stroke patients before and after being given integrated education with p-values of 0.000 (knowledge), 0.000 (attitude) and 0.001 (action). It can be concluded that integrated education affects the behavior of post-stroke patients. The provision of integrated education toaccording to the clinical pathway patientsof the patient's illness requires a joint commitment to the field of nursing services in order to improve the quality of service in hospitalsKeywords: Integrated Education, Knowledge, Attitude, Action